Standardization of recombinant Ancylostoma caninum cysteine protease 2 (rAcCP2) based indirect ELISA for serodiagnosis of hookworm infection in dogs - UKE, SUCHITA P; GARG, RAJAT; RAFIQI, SHAFIYA IMTIAZ; RAM, HIRA; KHURANA, K L; BANERJEE, P S (The Indian Journal of Animal Sciences, 2018)
Diagnosis of hookworm infection in dogs during pre-patentency or in pregnant bitches harbouring encysted larvae in tissues can be achieved by employing serological tests using proteins derived from somatic or excretorysecretory products of adult or larvae of Ancylostoma caninum. In the present study, cathepsin-B protease (AcCP2) of A. caninum, which helps in development of parasitism and nutrient digestion, was used to develop an indirect ELISA for detection of specific antibodies to A. caninum in dogs. The rAcCP2 (approx. 59.0 kDa) was cloned, expressed and purified under denaturing conditions. Serum samples of 20 known A. caninum positive and 15 known negative dogs were used for the standardization of indirect ELISA. The sensitivity and specificity of the assay was determined by using sera samples from 123 dogs (48 positive for A. caninum eggs in faeces and 75 faecal negative). Out of the 48 A. caninum faecal positive sera, 46 were tested positive (OD > 0.306) by indirect ELISA; whereas, 14 out of 75 faecal negative samples were also tested positive (OD > 0.306) by indirect ELISA. Based on the results, the sensitivity and specificity of rAcCP2 based indirect ELISA was calculated to be 95.8% and 84.3%, respectively. No cross-reactions were observed with serum from dogs naturally infected with B. canis vogeli, B. gibsoni, E. canis, Dirofilaria immitis and Toxocara canis. The results of the present study indicate that indirect ELISA with rAcCP2 protein might be appropriate in large scale epidemiological screening and for serological diagnosis of A. caninum infection in dogs.